Global Prevalence of Diabetic Retinopathy and Projection of Burden through 2045: Systematic Review and Meta-analysis - Teo, Zhen Ling; Tham, Yih-Chung; Yan Yu, Marco Chak; Chee, Miao Li; Rim, Tyler Hyungtaek; Cheung, Ning; Bikbov, Mukharram M; Wang, Ya Xing; Tang, Yating; Lu, Yi; Hin Wong, Ian Yat; Wei Ting, Daniel Shu; et al. (Ophthalmology (Rochester, Minn.), 2021)
To provide updated estimates on the global prevalence and number of people with diabetic retinopathy (DR) through 2045. The International diabetes federation (IDF) estimated the global population with diabetes mellitus (DM) to be 463 million in 2019 and 700 million in 2045. DR remains a common complication of DM and a leading cause of preventable blindness in the adult working population. We conducted a systematic review using PubMed, Medline, Web of Science and Scopus for population-based studies, published up to March 2020. Random effect meta-analysis with logit transformation was performed to estimate global and regional prevalence of DR, vision-threatening DR (VTDR), and clinically significant macular edema (CSME). Projections of DR, VTDR and CSME burden were based on population data from the IDF Atlas 2019. We included 59 population-based studies. Amongst individuals with diabetes, global prevalence was 22.27% (95% confidence interval [CI], 19.73-25.03%) for DR, 6.17% (95%CI 5.43 - 6.98%) for VTDR and 4.07% (95%CI 3.42 - 4.82%) for CSME. In 2020, the number of adults worldwide with DR, VTDR and CSME was estimated to be 103.12, 28.54 and 18.83 million, respectively; and by 2045, is projected to increase to 160.50, 44.82 and 28.61 million, respectively. DR prevalence was highest in Africa (35.90%), and North American and Caribbean regions (33.30%); and lowest in South and Central America region (13.37%). In meta-regression models adjusting for habitation type, response rate, study year and DR diagnostic method, Hispanics (odds ratio [OR], 2.92; 95% CI, 1.22-6.98) and Middle Easterners (OR, 2.44; 95% CI, 1.51-3.94) with diabetes were more likely to have DR, compared to Asians. The global DR burden is expected to remain high through 2045, disproportionately affecting countries in Middle East and North Africa, and Western Pacific. These updated estimates may guide DR screening, treatment, and public healthcare strategies.